Universal fluorescence in situ hybridization (FISH) protocol for mapping repetitive DNAs in insects and other arthropods - Cabral-de-Mello, Diogo Cavalcanti; Marec, František (Molecular genetics and genomics, 2021)
Repetitive DNAs comprise large portion of eukaryote genomes. In genome projects, the assembly of repetitive DNAs is challenging due to the similarity between repeats, which generate ambiguities for alignment. Fluorescence in situ hybridization (FISH) is a powerful technique for the physical mapping of various sequences on chromosomes. This technique is thus very helpful in chromosome-based genome assemblies, providing information on the fine architecture of genomes and their evolution. However, various protocols are currently used for FISH mapping, most of which are relatively laborious and expensive, or work properly only with a specific type of probes or sequences, and there is a need for a universal and affordable FISH protocol. Here we tested a FISH protocol for mapping of different DNA repeats, such as multigene families (rDNAs, U snDNAs, histone genes), satellite DNAs, microsatellites, transposable elements, DOP-PCR products, and telomeric motif (TTAGG)n, on the chromosomes of various insects and other arthropods. Different cell types and stages obtained from diverse tissues were used. The FISH procedure proved high quality and reliable results in all experiments performed. We obtained data on the chromosomal distribution of DNA repeats in representatives of insects and other arthropods. Thus, our results allow us to conclude that the protocol is universal and requires only time adjustment for chromosome/DNA denaturation. The use of this FISH protocol will facilitate studies focused on understanding the evolution and role of repetitive DNA in arthropod genomes.
Keywords: mapování chromozomů; Cytogenetics; DNA repeats; hmyz; In Situ Hybridization, Fluorescence; Evolution, Molecular; repetitivní sekvence nukleových kyselin; FISH protocol; DNA; telomery; molekulární evoluce; Multigene Family; Arthropods; členovci; Genome structure; Insecta; Repetitive Sequences, Nucleic Acid; hybridizace in situ fluorescenční; Fluorescence; Chromosomes; zvířata; multigenová rodina; Chromosome Mapping; Arthropoda; Animals; Telomere; fluorescence